Hadith #71 - Sahih al-Bukhari - Mu'awiya bin Hadeej (Sahih al-Bukhari)
I heard Allah’s Messenger (ﷺ) saying, “If Allah wants to do good to a person, He makes him comprehend the religion. I am just a distributor, but the grant is from Allah. (And remember) that this nation (true Muslims) will keep on following Allah’s teachings strictly and they will not be harmed by any one going on a different path till Allah’s order (Day of Judgment) is established.”
Grade: Sahih

Hadith #573 - Sahih al-Bukhari - Mu'awiya bin Hadeej (Sahih al-Bukhari)
You offer a prayer which I did not see being offered by Allah’s Messenger (ﷺ) when we were in his company and he certainly had forbidden it (i.e. two rak`at after the `Asr prayer).
Grade: Sahih

Hadith #1668 - Sahih al-Bukhari - Mu'awiya bin Hadeej (Sahih al-Bukhari)
I cut short the hair of Allah’s Messenger (ﷺ) with a long blade.
Grade: Sahih

Hadith #2349 - Sahih al-Bukhari - Mu'awiya bin Hadeej (Sahih al-Bukhari)
I heard Al-Bara’ bin `Azib saying, “The Prophet (ﷺ) orders us to do seven things and prohibited us from doing seven other things.” Then Al-Bara’ mentioned the following:– (1) To pay a visit to the sick (inquiring about his health), (2) to follow funeral processions, (3) to say to a sneezer, “May Allah be merciful to you” (if he says, “Praise be to Allah!”), (4) to return greetings, (5) to help the oppressed, (6) to accept invitations, (7) to help others to fulfill their oaths
Grade: Sahih

Hadith #2988 - Sahih al-Bukhari - Mu'awiya bin Hadeej (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “If Allah wants to do good for somebody, he makes him comprehend the Religion (i.e. Islam), and Allah is the Giver and I am Al-Qasim (i.e. the distributor), and this (Muslim) nation will remain victorious over their opponents, till Allah’s Order comes and they will still be victorious.”
Grade: Sahih

Hadith #3486 - Sahih al-Bukhari - Mu'awiya bin Hadeej (Sahih al-Bukhari)
I heard the Prophet (ﷺ) saying, “A group of people amongst my followers will remain obedient to Allah’s orders and they will not be harmed by anyone who will not help them or who will oppose them, till Allah’s Order (the Last Day) comes upon them while they are still on the right path.”
Grade: Sahih

Hadith #4625 - Sahih al-Bukhari - Mu'awiya bin Hadeej (Sahih al-Bukhari)
Allah’s Messenger (ﷺ), said, “Recite if you wish: Would you then if you were given the authority.” (47.22)
Grade: Sahih

Hadith #7175 - Sahih al-Bukhari - Mu'awiya bin Hadeej (Sahih al-Bukhari)
I heard the Prophet (ﷺ) saying, “A group of my followers will keep on following Allah’s Laws strictly and they will not be harmed by those who will disbelieve them or stand against them till Allah’s Order (The Hour) will come while they will be in that state.”
Grade: Sahih